Deserving Poor and the Desirability of Minimum Wage Rules - Tomer Blumkin; Leif Danziger (Center for Economic Studies and ifo Institute (CESifo), 2014)
In this paper we provide a novel justification for the use of minimum wage rules to supplement the optimal tax-and-transfer system. We demonstrate that if labor supply decisions are concentrated along the intensive margin and employment is efficiently rationed, a minimum wage rule can be socially beneficial by serving as a tagging device that targets benefits to the deserving poor, defined as low-skilled workers exhibiting a weak taste for leisure.
Keywords: D60; H20; H50; 330; redistribution; minimum wage; efficient rationing